Debating fiscal solidarity in the EU: interests, values and identities in the legitimation of the Next Generation EU plan. Issue 3 (3rd April 2022) - Miró, Joan
ABSTRACT: The article departs from the assumption that issues of member state solidarity, particularly in crisis moments, undergird the stability of the EU by holding the key to its legitimation. Against this background, the article employs the tools of discourse analysis to study how European executives deliberated over the institution of new mechanisms of fiscal solidarity in response to the outbreak of the COVID-19 crisis, as well as how they later legitimised the agreed mechanisms. Having coded 1, 143 quotes from 21 office-holders drawn from national and international press, the article shows how, during the COVID-19 crisis management debate, diverging visions on what is the EU and why should EU solidarity be embraced developed along the Northern–Southern interstate cleavage. More importantly, it indicates how some trends towards the nationalisation, instead of Europeanisation, of EU deliberative dynamics might hinder the future establishment of deeper forms of fiscal integration.